FOSTERING PATRIOTISM AMONG STUDENTS IN THE CLASSROOM OF THE RUSSIAN LANGUAGE - Kamola Abdullayevna Shokarimova (Western European Studies, 2025)
The article deals with the essential grounds of “patriotism”, various aspects, features and risks of this social phenomenon. The values of patriotism, realized through the patriotic education system, become a factor of national security, provide social and political stability, prevent radicalism, if the complex scientific approach is applied, the complexity and responsibility of this direction of state policy is taken into account.
Keywords: patriotism; citizenship; youth